Fertility Care Provided by a Public Health Hospital to Viral-Infected Couples: A Case-Control Study - Figueiredo, S (2021)
Objective: To evaluate the results of ART (clinical pregnancies and baby home rates) in couples infected with HBV, HCV, HIV or mixed in a Referral center. Patients: The study is a retrospective case-control study comprising 1587 cycles/1064 couples in the control group and 237 cycles/164 couples in the infected group, submitted to in vitro fertilization, intracytoplasmic sperm injection and embryo transfer. Two branches from the infected group were created: the HIV subgroup, comprising couples with one or both partners infected with HIV-1 (84 cycles/67 couples), and the HCV subgroup, including at least one partner infected with HCV (45 cycles/29 couples). Results: The infected group presented higher infertility duration (P < 0.001) and so did the HCV subgroup (P < 0.001). Tubal infertility was increased in the infected group (P < 0.001), and in the HIV (P < 0.001) and HCV (P = 0.01) subgroups. Oocytes and oocytes in metaphase II numbers were lower in the infected group, but not in the HIV and HCV subgroups. Clinical pregnancy rate was lower in the infected group (25.74%) when compared to the control (34.66%), probably due to the contribution of HCV individuals (17.78%), but not of HIV (28.57%). Baby home rate was lower in the infected group (21.52%) relative to the control group (28.42%), but no differences were found in the HIV (27.38%) and HCV (15.56%) subgroups. Conclusions: Despite the low clinical pregnancy rate in the HCV subgroup, baby home rates did not change from control. These data seem promising for couples with viral infections who wish to conceive.